Spectrum of Haematological & Non Haematological Disorder Diagnosed by Bone Marrow Examination: A Study of 115 Cases (Medicine Today, 2022)
Introduction: Haematological and nonhaematological diseases affecting the bone marrow may be primarily or a secondarily spread to the marrow. In most of the cases, diagnosis can be arrived at by a detailed history, physical examination and few simple investigations. Bone marrow examination is a very useful tool in the diagnosis of hematological and non-hematological diseases.Materials and Methods: This retrospective study was done in the department of haematology, in a specialized diagnostic centre from July 2018 to July 2021. A total of 115 cases were included in this study. Clinical parameters were assessed, peripheral blood smear along with necessary haematological investigations were done.Results: Majority patient were male (70%). In total cases 44.4% patients were under 30 years of age. Among them 23(20%) were under 10 years. The most common indication for bone marrow examination was diagnosis & management of Acute Leukaemia 27(23.48%), Major presenting complaints were fever 49(42.61%), fatigue 46(40.0%) & bleeding manifestation 22(19.13%). On systemic examination, pallor was found in majority of the cases. Hematological malignancies were found in 77(66.96%) cases, non-malignant haematological disorders were found in 33(28.70%) cases. Acute leukaemic condition (ALL, AML) were the most common malignant conditions, 22(19.13%) & 17(14.78%) respectively. Most common nonmalignant haematological conditions were hypocellular marrow 17(14.78%).Conclusion: Acute Leukemia is a major indication of BME. Among the pathological condition malignant condition are commonly seen. And male are predominantly suffering more from haematological disorders than female. In majority cases acute leukaemic condition are seen in BME.Medicine Today 2022 Vol.34(1): 7-11